The Influence of Intrinsic Motivation and Democratic Leadership Style on Employees' Work Ethic: Evidence from the Civil Service Police Unit of Central Tapanuli Regency, Indonesia - Juita Meliana Sitompul; Mansur Tanjung; Mhd. Shafwan Koto (Journal of Economics, Management and Accounting (JEMA), 2026)
This study aims to analyze the influence of intrinsic motivation and democratic leadership style on employees' work ethic at the Civil Service Police Unit (SATPOL PP) of Central Tapanuli Regency. The study employed a quantitative approach with an associative research design. The population consisted of 302 employees, while 76 respondents were selected as the research sample using a sampling technique. Data were collected through Likert-scale questionnaires, interviews, documentation, and literature review. Data analysis was conducted using multiple linear regression with IBM SPSS Statistics version 21, including validity testing, reliability testing, classical assumption testing, partial (t-test), simultaneous (F-test), and coefficient of determination (R²). The results indicate that intrinsic motivation has a positive and significant effect on employees' work ethic, with a t-value of 4.950 and a significance value of 0.000. Democratic leadership style also has a positive and significant effect on employees' work ethic, with a t-value of 3.479 and a significance value of 0.001. Simultaneously, intrinsic motivation and democratic leadership style significantly influence employees' work ethic, with an F-value of 45.039 and a significance value of 0.000. The coefficient of determination (R²) of 0.552 indicates that intrinsic motivation and democratic leadership style explain 55.2% of the variance in employees' work ethic, while the remaining 44.8% is influenced by other variables outside the research model. These findings imply that strengthening employees' intrinsic motivation and implementing a democratic leadership style are important strategies for improving employees' work ethic within public sector organizations.